GENETIC ANALYSIS OF YIELD AND YIELD CONTRIBUTING TRAITS IN LINSEED (LINUM USITATISSIMUM L.) - NIMIT KUMAR,; SATISH PAUL, (The Bioscan, 2015)
Twelve hybrids of linseed generated by crossing of 4 lines and 3 testers in line × tester mating design were sown along with their seven parental lines to assess the extent of standard heterosis over standard check i.e. Nagarkot for yield and eleven component traits. Dominance genetic variance varied from 0.36 (straw yield per plant) to 315.13 (seed yield per plot) and higher than additive genetic variance for all traits except technical height. Out of 12 F 1 hybrids, seven crosses T-397 x Nagarkot (34.24%), T-397 x Himalsi-1 (8.31%), Chambal x Nagarkot (43.56%), Chambal x HimAlsi-1 (21.53%), Chambal x EC-541194 (22.54%), HimAlsi-2 x HimAlsi-1 (37.29 %) and HimAlsi-2 x EC-541194 (40.17 %) exhibited significant positive standard heterosis. for seed yield per plant which could be an excellent source for developing high yielding linseed genotypes.